Associations of multimorbidity and patient‐reported experiences of care with conservative management among elderly patients with localized prostate cancer. (6th July 2020) - Fiano, Ryan M.; Merrick, Gregory S.; Innes, Kim E.; Mattes, Malcolm D.; LeMasters, Traci J.; Shen, Chan; Sambamoorthi, Usha
Abstract: Background: Many elderly localized prostate cancer patients could benefit from conservative management (CM). This retrospective cohort study examined the associations of patient‐reported access to care and multimorbidity on CM use patterns among Medicare Fee‐for‐Service (FFS) beneficiaries with localized prostate cancer. Methods: We used linked Surveillance, Epidemiology, and End Results cancer Registry, Medicare Claims, and the Medicare Consumer Assessment of Healthcare Providers and Systems (MCAHPS) survey files. We identified FFS Medicare Beneficiaries (age ≥ 66; continuous enrollment in Parts A & B) with incident localized prostate cancer from 2003 to 2013 and a completed MCAHPS survey measuring patient‐reported experiences of care within 24 months after diagnosis (n = 496). We used multivariable models to examine MCAHPS measures (getting needed care, timeliness of care, and doctor communication) and multimorbidity on CM use. Results: Localized prostate cancer patients with multimorbidity were less likely to use CM (adjusted odds ratio (AOR)=0.42 (0.27‐ 0.66), P < .001); those with higher scores on timeliness of care (AOR = 1.21 (1.09, 1.35), P < .001), higher education attainment (3.21 = AOR (1.50, 6.89), P = .003), and impaired mental health status (4.32 = AOR (1.86, 10.1) P < .001) were more likely to use CM. Conclusion(s): Patient‐reported experience with timely care was significantly and positively associated with CM use. Multimorbidity was significantly and inversely associated with CM use. Addressing specific modifiable barriers to timely care along the cancer continuum for elderly localized prostate cancer patients with limited life expectancy could reduce the adverse effects of overtreatment on health outcomes and costs. Abstract : Timeliness of care was significantly and positively associated, and multimorbidity was significantly and inversely associated with conservative management patterns among localized prostate cancer patients. Addressing specific modifiable barriers to timely care along the cancer continuum could help reduce overtreatment of elderly localized prostate cancer patients with multimorbidity and limited life expectancy.